EFEKTIVITAS EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) SEBAGAI LARVASIDA NYAMUK Aedes spp. PADA OVITRAP - shella elvandari; irnawati marsaulina; evi naria (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Guava (Psidium guajava L.) is one of medicine plant which leaf has all kind of purpose. Guava leaf contains alkaloid, flavonoid, tanin, saponin and etherial oils which effect to kill mosquito larvae. The purpose of this research is to know the effectiveness of guava leaf extract as an Aedes spp. mosquito larvacide in ovitrap and the value of LC50 within 24 hours. This study is a quasi experiment. The method of research using Completely Randomized Design which consist 6 concentrations of guava leaf extract (0 ppm, 500 ppm, 2.500 ppm, 4.500 ppm, 6.500 ppm and 8.500 ppm) by 4 times repetition. Seven hundred and twenty (720) mosquito larvaes are used in 100 ml solution of guava leaf extract. Observation times of Aedes spp. mosquito larvae mortality are 2 hours, 12 hours and 24 hours. Data was analized using Friedman and Kruskal Wallis test with 95% of credibility and probit analysis. According to statistics result indicates average difference of Aedes spp. mosquito larvae death in various guava leaf extract concentration and all time observation is showed by p-value < 0,05. The result of probit analysis showing that LC50 of guava leaf extract on concentration 2.502,67 ppm. As larvacide, the toxicity of guava leaf is safe for non-target organism. The conclusion of this research is guava leaf extract contains chemical substance which can be used as larvacide that most effective on concentration 8.500 ppm (93,33% death percentage) and the amount of the dead Aedes spp. mosquito larvae descended after 12 hours. Guava leaf is expected to be an alternative on Aedes spp. mosquito larvae restraint.